An Item-Level Analysis of the Posttraumatic Stress Disorder Checklist and the Posttraumatic Growth Inventory and Its Associations With Challenge to Core Beliefs and Rumination - Ramos, Catarina; Leal, Isabel; Costa, Pedro Alexandre; Tapadinhas, Ana Rosa; Tedeschi, Richard G. (Frontiers in Psychology, 2018)
Background: Previous studies have found that rumination and core beliefs may have a predictive effect on PTSD and PTG among different samples. In addition, there is some evidence that these variables have different effects on PTSD and PTG, although the latter construct has been the target of a larger body of research and theoretical models. The main objective of the current study is to examine the effect of challenges to core beliefs, intrusive rumination, and deliberate rumination on PTSD and PTG, through an item-level analyses. Methods: The sample was composed of 205 Portuguese women who had been given a breast cancer diagnosis (M = 54.32, SD = 10.05), and who completed the following self-administered questionnaires: the Posttraumatic Stress Disorder Checklist (PCL-C); the Posttraumatic Growth Inventory (PTGI); the Core Beliefs Inventory; and the Event Related Rumination Inventory. Two multivariate multiple regression analyses, using each item of the PCL-C and the PTGI as dependent variables, were conducted. Results: The results demonstrated that challenges to core beliefs predict 17 of the 21 PTGI items and 12 of the 17 PCL-C items. All but one item of the PCL-C are predicted by intrusive rumination, while the variance of only 4 items of the PTGI are explained by deliberate rumination. Conclusions: These findings indicate that women with breast cancer who tend to display higher levels of intrusive rumination are more likely to report PTSD symptoms, and that an examination of one’s core beliefs is predictor of both positive and negative outcomes. In spite of the proven effect of challenges to core beliefs on both variables, this study suggests that this effect has only a minor influence on PTSD, in addition to confirming its major impact on PTG.